2016
DOI: 10.1128/jvi.01181-16
|View full text |Cite
|
Sign up to set email alerts
|

Viral FGARAT Homolog ORF75 of Rhesus Monkey Rhadinovirus Effects Proteasomal Degradation of the ND10 Components SP100 and PML

Abstract: Nuclear domain 10 (ND10) components restrict herpesviral infection, and herpesviruses antagonize this restriction by a variety of strategies, including degradation or relocalization of ND10 proteins. The rhesus monkey rhadinovirus (RRV) shares many key biological features with the closely related Kaposi's sarcoma-associated herpesvirus (KSHV; human herpesvirus 8) and readily infects cells of both human and rhesus monkey origin. We used the clustered regularly interspaced short palindromic repeatCas9 (CRISPR-Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Generation of knockout cell pools. Knockout cell pools were generated using the lentiCRISPRv2 system (37) as described previously (38), with the exception that transfection was carried out using polyethylenimine (PEI) MAX (Polysciences) (39). In short, BJAB cells were transduced with lentiviruses harboring the indicated sgRNAs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generation of knockout cell pools. Knockout cell pools were generated using the lentiCRISPRv2 system (37) as described previously (38), with the exception that transfection was carried out using polyethylenimine (PEI) MAX (Polysciences) (39). In short, BJAB cells were transduced with lentiviruses harboring the indicated sgRNAs.…”
Section: Methodsmentioning
confidence: 99%
“…Two monoclonal cell lines per target (nontargeting [sgNT-1] and EphA7 [sgEPHA7-3 and sgEPHA7-4]) were transduced with a lentivirus carrying an EphA7-Strep expression cassette (transcript variant 1 [NM_004440]) (pLenti-CMV-BLAST-EphA7-Strep) or an empty vector control. Lentiviral particles were generated as described previously (38), with the exception that transfection was carried out using PEI. Two days postransduction the selection antibiotic blasticidin (Invivogen) was added to a final concentration of 10 g/ml.…”
Section: Methodsmentioning
confidence: 99%
“…GAPDH served as an internal RNA loading control. 59 and 34 (lanes 3 and 7) did not express a detectable level of ORF50 protein. These data indicate that lack of ORF57 expression, at least in single-cell clones 6, 2, and 39, was not due to the lack of successful KSHV lytic induction but rather to the specific ORF57 KO from all copies of the virus genome.…”
Section: Figmentioning
confidence: 97%
“…Additionally, R12 protein expression during RRV vIRF-KO infection could restore the full disruption and loss of PML-NBs, suggesting a critical role for R12 in this process. A previous publication on PML-NB disruption by RRV implicated the RRV tegument protein encoded by ORF75 and found that while RRV infection of RhF cells resulted in a loss of SP100 protein by 8 hpi, PML protein was not lost until 24 hpi, and this could be rescued with cycloheximide treatment (24). Thus, the inhibition of R12 expression by cycloheximide treatment could explain why PML protein levels were rescued.…”
Section: Discussionmentioning
confidence: 90%